2013
DOI: 10.1055/s-0033-1342981
|View full text |Cite
|
Sign up to set email alerts
|

The Association of a Preschool Voice Education Program with Changes in Yelling Frequency

Abstract: Voice problems in children can occur as early as infancy. Early onset of voice problems can carry social and academic penalties, and negatively affect voice in adolescence or adulthood. Unfortunately, only 1% of school-aged children receive voice therapy despite a 6 to 24% prevalence of voice disorders in school-aged children. One alternative may be to use a classroom-based voice education curriculum to effectively reduce yelling frequency, the most common behavior associated with phonotrauma-related voice pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It is also a meaningful factor in involving parents in therapy and raising their awareness of its importance. [14][15][16][17] Preliminary research on the effectiveness of the application showed differences in the process of acquiring language skills depending on group affiliation. The result was obtained both in the time interval of 1-6 weeks and after 12 weeks of the intervention -the relationship concerned all analyzed groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a meaningful factor in involving parents in therapy and raising their awareness of its importance. [14][15][16][17] Preliminary research on the effectiveness of the application showed differences in the process of acquiring language skills depending on group affiliation. The result was obtained both in the time interval of 1-6 weeks and after 12 weeks of the intervention -the relationship concerned all analyzed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study suggest that vocal hygiene education can enhance children’s voice care knowledge. Marcus et al [27] provided encouraging findings that gaining knowledge about vocal hygiene can impact on their voice care practice. In their study, preschoolers received 4 half-hour sessions on voice production anatomy and physiology, and alternative strategies for phonotraumatic behavior of yelling.…”
Section: Discussionmentioning
confidence: 99%
“…12 As suggested in a companion article in this issue of Seminars, school-aged children who exhibit hoarseness may have a medical pathology or have established unhealthy voicing patterns before or during their preschool years. 13 It is interesting to note that one of the most common forms of "phonotraumatic behaviors" leading to voice disorders in children is yelling. [14][15][16][17][18][19][20] It is also a very noticeable sign of conflict in young children.…”
Section: Conflict Resolution In Children With Communication Disordersmentioning
confidence: 99%